Effects of the fe/Mn Weight ratio and cooling rate on the area fractions of α-AlFeSi AND β-AlFeSi Phases in Al-7.5Si-3.75Cu-0.5Mg-0.55Fe-xMn Aluminum alloy - Hernández Rodríguez, Alejandra Nohemí; Castro Román, M. de J.; Herrera Trejo, M.; Belmares Perales, S.; Orozco González, Pilar (Centar za informiranje željezare Sisak, 2014)
Iron is a common impurity present in commercial Al-Si alloys [1-3] and has consistently emerged as the impurity element that may be the most detrimental to the mechanical properties of these alloys [4]. When this element is combined with the aluminum and other alloying elements, iron intermetallic compounds are formed. The iron-bearing compounds that form during solidifi cation appear in a great variety of shapes and sizes and can generally be divided into three different morphologies: β-Al5FeSi-needles, α-Al15(Fe,Mn)3Si2-Chinese scripts and polyhedral and/or star-like crystals. The amount, size and shape of these iron compounds depend largely on the cooling conditions and on the chemical composition, especially the level of iron in the melt [5]. β-Al5FeSi-needles iron compounds have usually been considered most detrimental to the mechanical properties of Al-Si alloys because of the brittle features and stress concentration caused by the needle-like morphology. This kind of intermetallics